The Coping Mechanism of Class Mayors of Senior High School HUMSS Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This Study at Bestlink College of the Philippines examined the coping strategies of senior highschool HUMSS class mayors.According to the study's findings, the majority of class mayors are female, and that occursbetween the ages of 17 and 19. Additionally, it is stated that by accomplishing their giventasks, they have improved their academic performance and time management. Class mayors,however, have faced challenging circumstances as student leaders.The study's recommendation was to believe in your ability to complete the task at hand ratherthan putting unnecessary pressure on yourself to complete it. Your body responds to what youthink.
Keywords: Education